Digital society and society 5.0: Urgent issues for digital social transformation in Vietnam - Hoang H Nguyen; Huan V Tran (Faculty of Social and Political Science, Universitas Airlangga, 2022)
Society has been undergoing a complex transformation from a traditional society to a modern, post-modern society with a new state of social history - “digital society”, “society 5.0” based on the development of digital technology to help connect things and unprecedentedly change our life. This article uses a qualitative method by collecting, reviewing many Vietnamese and international scientific documents to focus on analyzing three contents: (1) history, concept, and nature of “digital society”, “society 5.0”, (2) proposing an overall model of a digital society suitable to the reality of Vietnam from the overall “digital society” model of some countries in the Asia-Pacific region and “society 5.0”, (3) urgent issues in the process of implementing the goal of building a “digital society” in Vietnam by 2030. These issues discussed are also valuable for reference for countries whose context, culture, and development level are similar to Vietnam’s to adapt to digital social transformation. The important result of the study is the proposal of the overall model to build the digital society with four specific criteria: digital economy, digital government, digital culture, and digital society for Vietnamese practice and implications for countries at the same level of development.